Association between loss of hypercoagulable phenotype, clinical features and complement pathway consumption in COVID-19 - Kasugai, Daisuke; Tanaka, Taku; Suzuki, Takako; Ito, Yoshinori; Nishida, Kazuki; Ozaki, Masayuki; Kutsuna, Takeo; Yokoyama, Toshiki; Kaneko, Hitoshi; Ogata, Ryo; Matsui, Ryohei; Goshima, Takahiro; et al. (Frontiers in Immunology, 2024)
Background: Coronavirus disease 2019 (COVID-19) features a hypercoagulable state, but therapeutic anticoagulation effectiveness varies with disease severity. We aimed to evaluate the dynamics of the coagulation profile and its association with COVID-19 severity, outcomes, and biomarker trajectories. Methods: This multicenter, prospective, observational study included patients with COVID-19 requiring respiratory support.Rotational thromboelastometry findings were evaluated for coagulation and fibrinolysis status. Hypercoagulable status was defined as supranormal range of maximum clot elasticity in an external pathway. Longitudinal laboratory parameters were collected to characterize the coagulation phenotype. Results: Of 166 patients, 90 (54%) were severely ill at inclusion (invasive mechanical ventilation, 84; extracorporeal membrane oxygenation, 6). Higher maximum elasticity (P=0.02) and lower maximum lysis in the external pathway (P=0.03) were observed in severely ill patients compared with the corresponding values in patients on non-invasive oxygen supplementation. Hypercoagulability components correlated with platelet and fibrinogen levels. Hypercoagulable phenotype was associated with favorable outcomes in severely ill patients, while normocoagulable phenotype was not (median time to recovery, 15 days vs. 27 days, P=0.002), but no significant association was observed in moderately ill patients. In patients with severe COVID-19, lower initial C3, minimum C3, CH50, and greater changes in CH50 were associated with the normocoagulable phenotype.Changes in complement components correlated with dynamics of coagulation markers, hematocrit, and alveolar injury markers. Conclusions: While hypercoagulable states become more evident with increasing severity of respiratory disease in patients with COVID-19, normocoagulable phenotype is associated with triggered by alternative pathway activation and poor outcomes.